2016
DOI: 10.1136/eb-2016-102430
|View full text |Cite
|
Sign up to set email alerts
|

Exercising control over bipolar disorder

Abstract: Following extensive research exercise has emerged as an effective treatment for major depressive disorder, and it is now a recognised therapy alongside other interventions. In contrast, there is a paucity of research examining the therapeutic effects of exercise for those with bipolar disorder. Given that dysfunctional reward processing is central to bipolar disorder, research suggests that exercise can perhaps be framed as a reward-related event that may have the potential to precipitate a manic episode. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“… 22 However, most research in this area is based on first-episode patients and/or excludes participants with treatment-resistant depression and BD. 39 Critically, this work also rarely evaluates the impact of exercise in terms of clinical outcomes, nor is there research on exercise type, intensity, the role of social support and/or the impact of exercise on functional outcomes. 40 In the current study, we found engagement in a group running programme improved mood symptoms including depression, anxiety and stress in participants with complex mood disorders, over a period of 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“… 22 However, most research in this area is based on first-episode patients and/or excludes participants with treatment-resistant depression and BD. 39 Critically, this work also rarely evaluates the impact of exercise in terms of clinical outcomes, nor is there research on exercise type, intensity, the role of social support and/or the impact of exercise on functional outcomes. 40 In the current study, we found engagement in a group running programme improved mood symptoms including depression, anxiety and stress in participants with complex mood disorders, over a period of 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the cumulative incidence of bipolar disorder among women in the fastest skiing group reached the same level as those not participating in the ski race. Several studies have suggested that heavy exercise may provoke manic episodes in individuals prone to bipolar disorder (Malhi and Byrow 2016 ). Nevertheless, when excluding all individuals who developed bipolar disorder during the first 5 years this difference became nonsignificant.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggested that exercise, either as monotherapy or in combination with antidepressant medication, was associated with decreased relapse rate, depending on the depression severity and associated symptoms . Though some studies focused on exercise monotherapy, others evaluated exercise as an adjuvant therapy to medical treatment . However, mortality and CHD outcomes had not been studied before in this specific population .…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Though some studies focused on exercise monotherapy, [29][30][31][32] others evaluated exercise as an adjuvant therapy to medical treatment. [33][34][35] However, mortality and CHD outcomes had not been studied before in this specific population. 8 Our current study adds to the literature related to CHD prevention in patients with depression by showing a strong, consistent, and inverse relationship of increased exercise capacity with lower risk of ACM and nonfatal MI.…”
Section: Discussionmentioning
confidence: 99%